Politics and bureaucracy in urban governance: The Indian experience - Mukhopadhyay, Asok (1996)
Giving background of structural patterns of urban governance in India and its broad features, the author focuses on analysing roles of municipal bureaucracy and the elected councillors to provide an appreciation of councillor-bureaucrat interface drawing support from findings of some of the well-known recent empirical studies on the subject. Making a comparative assessment of different systems of urban governance vis-a-vis urban politics, he presents advantages of the Mayor-in-Council system based on its success in handling urban politics in Calcutta. - Reproduced.
Keywords: Civil service - India - West Bengal; Municipal officials and employees - India - West Bengal; Local government